Mortality and morbidity rates in patients undergoing emergency laparotomy: an analysis in a tertiary care hospital - Manoj P,; Shashikumar HB,; Fathimath Shihana, (Asian Journal of Medical Sciences, 2022)
Background: Emergency Laparotomy is a complex and often time-critical surgical procedure associated with significant morbidity and mortality. Emergency abdominal surgery is performed in most hospitals, and acute laparotomy is considered a high-risk procedure with significant mortality rates ranging from 14% to 20%. This study is done to assess the mortality and morbidity rates in patients undergoing emergency laparotomy at a tertiary care hospital over a period of 1 year and to identify risk factors associated with it. Aims and Objectives: To assess the mortality and morbidity rates in patients undergoing emergency laparotomy at a tertiary care hospital. Materials and Methods: This is a prospective observational study conducted in the department of general surgery at KR hospital during the period of January 2020 to December 2020. All the patients who underwent emergency laparotomy were included in the study. Patient was followed during the pre-operative, intraoperative and post operative period and demographic data, comorbidities, habits were collected pre-operatively. Post-operatively, the complications were identified and classified based on the Clavien-Dindo classification. Cox proportional hazards model was used to identify risk factors for mortality and morbidity. Results: A total of 478 patients underwent emergency laparotomy, of whom 18% had surgical complications and 23% had medical complications. The overall 30-day mortality was 20.3%. The overall death rate within 24 h of surgery was assessed. Several risk factors for 30-day mortality were identified: age, ASA >3, performance score, etc. Conclusion: A complete analysis of complications and mortality in a consecutive group of patients undergoing laparotomy was done and found that almost one in five patients died after emergency laparotomy. Predictors of poor outcome and several risk factors for mortality and morbidity were identified.